2021
DOI: 10.3390/toxins13040246
|View full text |Cite
|
Sign up to set email alerts
|

Uremic Toxins and Blood Purification: A Review of Current Evidence and Future Perspectives

Abstract: Accumulation of uremic toxins represents one of the major contributors to the rapid progression of chronic kidney disease (CKD), especially in patients with end-stage renal disease that are undergoing dialysis treatment. In particular, protein-bound uremic toxins (PBUTs) seem to have an important key pathophysiologic role in CKD, inducing various cardiovascular complications. The removal of uremic toxins from the blood with dialytic techniques represents a proved approach to limit the CKD-related complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…The target 2m predialysis level of <30mg/L was met in 70% of our study population, while 36.67% even had predialysis β 2 m level < 25ml/L [11,[23][24][25][26]. The highest β2m removal rate in our study population was achieved with FX CorDiax 800 dialyzer, even though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The target 2m predialysis level of <30mg/L was met in 70% of our study population, while 36.67% even had predialysis β 2 m level < 25ml/L [11,[23][24][25][26]. The highest β2m removal rate in our study population was achieved with FX CorDiax 800 dialyzer, even though the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies have demonstrated that the average β2m removal rate ranges from 50-60% with regular high-flux HD, to 70% with medium cut-off membranes, to 80-85% with high volume (Vconv > 22 L / dialysis session) post-dilution OL-HDF [23][24][25][26]. The somewhat lower β2m reduction ratio achieved with post-dilution OL-HDF in our study population, ranging from 70.04-74.69%, can be explained by lower than average Vconv and Qb in our study population (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the associated uremic toxins originate in the intestines by bacterial metabolization of dietary products. Some of these intestinally generated uremic toxins are bound to proteins in the circulation, and their removal by dialysis is expensive and remains insufficient [24,25]. Alternative measures to decrease levels of these uremic toxins, preferably targeting uremic toxins at their origin, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The poor removal of PBUTs with conventional HD is evidenced by the fact that pre-dialysis levels of IS and pCS have been found to be as much as 116-fold and 41-fold higher, respectively, than in age-matched healthy controls, while pre-dialysis concentrations of non-protein-bound solutes with comparable molecular weight, such as urea and creatinine, were only 5- and 13-fold higher, respectively [ 8 ]. Strong protein-binding results in a low reduction ratio of 20 to 35% for prototypical PBUTs [ 9 ], while the reduction ratio for small non-protein-bound solutes such as urea is around 80% during a conventional 4 h hemodialysis session [ 10 ]. The reduction ratio of a solute is a measure of dialysis session efficacy and indicates the percentage reduction in total serum concentration for this solute during a given dialysis duration.…”
Section: Introductionmentioning
confidence: 99%